Environmental Factors Causing Stress in Avicennia marina Mangrove in Rabigh Lagoon Along the Red Sea: Based on a Multi-Approach Study - Aljahdali, Mohammed O.; Alhassan, Abdullahi B.; Zhang, Zhaohui (Frontiers in Marine Science, 2021)
Lagoons along the Red Sea are socio-economically important but most vulnerable ecosystems. Strong evaporation, strengthened due to global warming, leads to high salinity and high temperature in surface water, which exacerbate physiological stress in mangroves. Rabigh Lagoon is characterized by unusually large spatial differences in nutrient dynamics and physicochemical parameters. We conducted a multi-approach study to demonstrate how environmental factors cause growth retardation and stress in mangroves. There were significant variations (P < 0.05) in water salinities and temperatures, nitrogen and phosphorus abundance in sediments, and antioxidants in mangroves among 8 sites across the lagoon. Salinity and water temperature rapidly increased from the northern where Red Sea seawater enters to the southern end, but dissolved oxygen declined. High salinity (44.9), high surface water temperature (28.8°C) and relatively high nutrients at the southern end of the lagoon (S8) corresponded to high concentrations of antioxidants. High δ13C (−12.4‰) and δ15N (4.9‰) in the sediments at S8 also reveal relatively high nutrient level due to stagnant water, camel grazing, and runoff bringing in fertilizer from agriculture activities in the catchments during seasonal flooding events. Principal component analyses showed that N and P limitation at the lagoon entrance is the leading cause for mangrove stress, while high salinity, temperature, and low dissolved oxygen are the predominant factors for high antioxidants concentrations at the southern end of the lagoon.